Abstract 241: Outcomes of Statins Post‐Endovascular Thrombectomy in Ischemic Stroke - Nader El Seblani; Nandakumar Nagaraja (Stroke: Vascular and Interventional Neurology)
Introduction Acute large vessel occlusions (LVOs) represent one‐third of acute ischemic strokes (AIS). LVOs are associated with high mortality and severe functional deficits. Several factors have been reported to play a role in improving outcomes after Endovascular Thrombectomy (EVT). Previous animal studies indicated that statins may have a protective effect on vessel wall injury caused by mechanical thrombectomy. We conducted a retrospective study to analyze whether pretreatment with statins influence the clinical and safety outcomes of EVT in AIS. Methods We conducted a retrospective observational study using the TriNetX database, a global health research network that provides access to electronic medical records retrieved from multiple international healthcare organizations but predominantly from the United States. We collected data about patients' diagnoses (using ICD‐10‐CM codes), medical procedures, medications, and demographics. Investigators were blinded to patients’ personal information or identification of participating healthcare organizations. Our study included adult patients with AIS who received EVT treatment (either extirpation or dilation procedure) between January 4, 2018, and December 31, 2022. The study patients were categorized into two groups based on whether or not they were on statins (Rosuvastatin, Simvastatin, Pravastatin, Atorvastatin, Lovastatin or Pitavastatin) during 3 months prior to hospitalization for AIS. Thirty‐day timepoint assessment was chosen to analyze the primary outcome (all‐cause mortality) and secondary outcomes [intracerebral hemorrhage (ICH), subarachnoid hemorrhage (SAH), decompressive hemicraniectomy procedure (DHC), and aspiration pneumonia]. The chi‐square χ2 test was used to analyze baseline characteristics for categorical variables and the independent‐sample t‐test was used for continuous variables. Matching propensity scores (with a tolerance level of 0.01 and the difference between propensity scores ≤ 0.1) were used to control differences in the comparison cohorts. Results We identified 11,972 patients who received EVT for LVO ischemic stroke. A total of 5,839 patients were on statins during 3 months prior to EVT and 6,133 were not on statins. After 1:1 propensity matching, 1,602 patients were included in each group. Kaplan‐Meier survival analysis showed the 30‐day mortality rates were significantly less for patients who were on statins compared to those who were not and with higher survival probability [87.2% vs. 77.5%, hazard ratio 0.54; confidence interval (CI): 0.45,0.64]. In comparison to EVT patients who were not on statins, those who were on statins had significantly lower rates of ICH [9.9 vs 14.1%; odds ratio (OR) 0.67; 95% CI (0.53,0.84)], lower rates of SAH [4.1 vs. 6.3%; OR 0.64; 95% CI (0.46,0.89)] and lower rates of aspiration pneumonia [5.6 vs 8.3%; OR 0.66; 95% CI (0.50,0.88)]. There was no significant difference in rates of DHC in the statins group in comparison to patients who were not on statins [1.8 vs 2.4%; OR 0.74; 95% CI (0.45,1.22)]. Conclusion Pretreatment with statins was associated with significantly better survival, less bleeding risks, and lower complication rates in LVO ischemic strokes post‐EVT. Future studies may help examine the differential effects of statin type and dose intensity on LVO strokes treated with EVT.